STUDY OF CHANGES IN PRODUCTIVITY INDEX OF SELECTED INDIAN BANKS BY APPLYING DEA BASED MALMQUIST INDEX TECHNIQUE (International Journal of Food and Nutritional Sciences, 2022)
Abstract: The Malmquist Productivity Index (MI) is a DEA based valuable tool for assessing and comparing the efficiency of banks over time. Its ability to break down productivity changes into specific components makes it especially useful for understanding the underlying factors influencing a bank's performance. The Indian banking industry comprises of public sector banks, private sector banks and foreign banks. Over the number of years, the performance of Indian banks has been influenced by various factors, including economic conditions, regulatory changes, and global events. The Reserve Bank of India (RBI) introduced various regulatory measures to strengthen the banking system, enhance transparency, and ensure better risk management practices.